SCIENTIFIC VIEWS ON THE FORMATION OF COLLABORATIVE ACTIVITIES IN EDUCATION - Taylakova Gulnoz Mamatkarimovna (Bright Mind Publishing, 2025)
This scientific article provides an in-depth DSc-level examination of the theoretical and methodological foundations underlying the formation of collaborative activity in education, integrating psychological, pedagogical, and sociocognitive perspectives to analyze how cooperative learning functions as a critical mechanism for enhancing student interaction, communication, cognitive development, motivation, and collective problem-solving abilities. Structured according to the IMRaD model and aligned with OAK academic requirements, the study explores the multidimensional structure of collaboration, including its cognitive, sociocommunicative, reflective, motivational, and organizational components, and investigates how contemporary approaches—such as constructivism, Vygotskian social learning theory, cooperative learning models (Johnson & Johnson, Slavin), project-based collaboration, peer-instruction frameworks, and digital cooperative environments—shape its development. The analysis highlights that collaboration in education not only facilitates academic achievement but also strengthens social capital, deepens metacognitive awareness, enhances creativity, and prepares learners for complex real-world tasks that require coordinated group effort. The findings support the conclusion that collaborative activity is not merely a pedagogical technique but a foundational paradigm in modern education, offering a robust methodological basis for curriculum design, instructional strategies, and innovative pedagogical practice.
Keywords: Collaboration, cooperative learning, constructivism, social learning, group interaction, educational psychology.